Histone demethylase JMJD2D promotes the self-renewal of liver cancer stem-like cells by enhancing EpCAM and Sox9 expression - Deng, Yuan (J Biol Chem, 2020)
Cancer stem-like cells (CSCs) contribute to the high rate of tumor heterogeneity, metastasis, therapeutic resistance, and recurrence. Histone lysine demethylase 4D (KDM4D or JMJD2D) is highly expressed in colon and liver tumors, where it promotes cancer progression; however, the role of JMJD2D in CSCs remains unclear. Here, we show that JMJD2D expression was increased in liver cancer stem-like cells (LCSCs); downregulation of JMJD2D inhibited the self-renewal of LCSCs in vitro and in vivo and inhibited the lung metastasis of LCSCs by reducing the survival and the early lung seeding of circulating LCSCs. Mechanistically, JMJD2D promoted LCSC self-renewal by enhancing the expression of CSC markers EpCAM and Sox9; JMJD2D reduced H3K9me3 levels on the promoters of EpCAM and Sox9 to enhance their transcription via interaction with β-catenin/TCF4 and Notch1 intracellular domain, respectively. Restoration of EpCAM and Sox9 expression in JMJD2D-knockdown liver cancer cells rescued the self-renewal of LCSCs. Pharmacological inhibition of JMJD2D using 5-c-8HQ reduced the self-renewal of LCSCs and liver cancer progression. Collectively, our findings suggest that JMJD2D promotes LCSC self-renewal by enhancing EpCAM and Sox9 expression via Wnt/β-catenin and Notch signaling pathways and is a potential therapeutic target for liver cancer.